Caring bodies: Women’s invisible labor and Gendered Caregiving in Turkish Disability context - Doğruel, Fulya (ANDULI, Revista Andaluza de Ciencias Sociales, 2025)
Disability care provides essential support to individuals unable to manage daily life independently. Women caring for children with disabilities often perform informal caregiving alongside domestic duties, which makes their work more labor-intensive and reinforces gendered labor divisions. In Turkey, caregiving is largely seen as women’s responsibility, shaped by traditional norms and policies. This study explores the experiences of 18 female caregivers in Bandırma, Balıkesir province, from a gender and citizenship perspective. It establishes that caregiving, without institutional support, exacerbates women’s economic hardship, social isolation, and physical exhaustion, while also limiting access to citizenship rights. While financial assistance, such as the home carer’s allowance, offers relief, it reinforces traditional roles and limits caregivers’ personal and professional opportunities. Framing care labor within broader debates on gender and citizenship, this study emphasizes the urgency of a rights-based approach that includes social security, accessible services, and legal protections to reduce caregivers’ burdens, foster inclusion, and ensure the well-being of caregivers and care recipients.